Ficopomatus talehsapensis, a new brackish-water species (Polychaeta: Serpulidae: Ficopomatinae) from Thailand, with discussions on the relationships of taxa constituting the subfamily, opercular insertion as a taxonomic character and their taxonomy, a key to its taxa, and their zoogeography - Pillai, T. Gottfried (Zootaxa, 2008)
A new brackish-water serpulid polychaete species belonging to the genus Ficopomatus from Thailand is described. It had previously been identified as another known species belonging to the same genus. Taxonomic problems within the subfamily Ficopomatinae to which it belongs and the relationship of the genus Marifugia and its single known species which occurs in freshwater are discussed. While the other known genera of the subfamily possess seven thoracic chaetigers, Marifugia has six, but agrees with the former with regard to all other important characters. Likewise, among typically marine taxa, the genus Pomatoleios has six thoracic characters but agrees with the genera Pomatoceros and Spirobranchus with regard to all other important characters. As there are also other known serpulid genera having six thoracic chaetigers, an analysis was undertaken of 10 genera, six of them having six thoracic chaetigers and the remaining four seven. It revealed that Marifugia is the sister to the clade containing the other two genera of the Ficopomatinae (Neopomatus and Ficopomatus) and Pomatoleios is sister to the clade containing Pomatoceros and Spirobranchus. The usefulness of opercular insertion/derivation from a particular branchial radiole as a character in serpulid taxonomy is discussed. As observed in adults and juveniles of species belonging to ficopomatine genera, as well on available evidence on post-larval development, their opercular insertion is in the position of the first branchial radiole, unlike in genera such as Pomatoceros and Hydroides where it is on the second. A key to the known taxa of the subfamily is provided. Although they may be geographically separated by oceanic and/or terrestrial barriers, their common characters, including their ability to survive and propagate in their respective typically non-marine habitats, are indicative of their monophyly.